2020
DOI: 10.21203/rs.3.rs-80915/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics, Management, and Outcomes of Elderly Patients With Diabetes in a COVID-19 Unit: Lessons Learned.

Abstract: BackgroundDiabetes may affect in-hospital mortality of patients with Coronavirus disease 2019 (COVID-19). We have retrospectively evaluated clinical characteristics, diabetes management, and outcomes in a sample of COVID-19 patients with diabetes admitted to our hospital. MethodsAll patients admitted to the Infectious Diseases Unit from March 28th, 2020, to June 16th, 2020, were enrolled. Clinical information and biochemical parameters were collected at the time of admission. Patients were ranked according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…-T2DM treated with insulin had a decreased risk of COVID-19 infection requiring hospitalization (85) Multi-injection insulin therapy or continuous intravenous infusion by a syringe pump in acutely serious hospitalized patients with COVID-19 (116) ACE2, angiotensin-converting enzyme 2; COVID-19, coronavirus disease 2019; DM, diabetes mellitus; mTOR, mammalian target of rapamycin; ROS, reactive oxygen species; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2; TNF-a, tumor necrosis factor alpha.…”
Section: Metforminmentioning
confidence: 99%
See 1 more Smart Citation
“…-T2DM treated with insulin had a decreased risk of COVID-19 infection requiring hospitalization (85) Multi-injection insulin therapy or continuous intravenous infusion by a syringe pump in acutely serious hospitalized patients with COVID-19 (116) ACE2, angiotensin-converting enzyme 2; COVID-19, coronavirus disease 2019; DM, diabetes mellitus; mTOR, mammalian target of rapamycin; ROS, reactive oxygen species; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2; TNF-a, tumor necrosis factor alpha.…”
Section: Metforminmentioning
confidence: 99%
“…Some evidence has demonstrated that patients with severe COVID-19 and DM have a higher insulin requirement (92,93), which may be explained by the dysfunction of beta-cells or the high inflammatory process induced by the virus. For these reasons, the best therapeutic choice for these patients is multi-injection insulin therapy or continuous intravenous infusion by syringe pump (116) with adequate enteral nutrition or regular oral food intake. Importantly, the use of insulin has some disadvantages, among which is the need to closely monitor the patient's glucose levels to avoid hypoglycemia (132,133).…”
Section: Insulinmentioning
confidence: 99%